Expression analysis of miRNA hsa‐let7b‐5p in naso‐oropharyngeal swabs of COVID‐19 patients supports its role in regulating ACE2 and DPP4 receptors. Issue 19 (8th September 2022) - Latini, Andrea; Vancheri, Chiara; Amati, Francesca; Morini, Elena; Grelli, Sandro; Claudia, Matteucci; Vita, Petrone; Colona, Vito Luigi; Murdocca, Michela; Andreoni, Massimo; Malagnino, Vincenzo; Raponi, Massimiliano; et al.
Abstract: Severe Acute Respiratory Syndrome Coronavirus‐2 (SARS‐CoV‐2) is the novel coronavirus responsible for worldwide coronavirus disease (COVID‐19). We previously observed that Angiotensin‐converting enzyme 2 (ACE2) and Dipeptidyl peptidase‐4 (DPP4) are significantly overexpressed in naso‐oropharyngeal swabs (NPS) of COVID‐19 patients, suggesting their putative functional role in the disease progression. ACE2 and DPP4 overexpression in COVID‐19 patients may be associated to epigenetic mechanism, such as miRNA differential expression. We investigated if hsa‐let7b‐5p, reported to target both ACE2 and DPP4 transcripts, could be involved in the regulation of these genes. We verified that the inhibition and overexpression of hsa‐let7b‐5p matched to a modulation of both ACE2 and DPP4 levels. Then, we observed a statistically significant downregulation (FC = −1.5; p  < 0.05) of hsa‐let7b‐5p in the same COVID‐19 and control samples of our previous study. This is the first study that shows hsa‐let7b‐5p low expression in naso‐oropharyngeal swabs of COVID‐19 patients and demonstrates a functional role of this miR in regulating ACE2 and DPP4 levels. These data suggest the involvement of hsa‐let7b‐5p in the regulation of genes necessary for SARS‐CoV‐2 infections and its putative role as a therapeutic target for COVID‐19.